(untitled) (Sociologisk Forskning, 2022)
Previous research has demonstrated that many children experience racism in the Swedish school system, a public institution that formally aims to combat all forms of discrimination. The question posed in this article is how racism can endure despite the school system’s anti-racist agenda. Everyday racism is examined from children’s perspectives, based upon eight focus groups with primary school pupils and a group of 11-year-old co-researchers who contributed to the interview planning and data analysis. The focus group discussions show that while everyday racism is typically concealed, invisible to teachers and other adults, racial microaggressions are nevertheless often detected by children themselves. The analysis reveals that children have the intention to speak up against everyday racism, but lack the necessary support and protection from adults. The article concludes that to fight racism in the Swedish school environment, adults must learn how everyday racism operates and in that learning process actively consult children for their perspectives.